Self-release of CLIP in peptide loading of HLA-DR molecules - Kropshofer, Harald; Vogt, Anne B.; Stern, Lawrence J.; Hämmerling, Günter J. (Science, 1995)
The assembly and transport of major histocompatibility complex (MHC) class II molecules require interaction with the invariant chain. A fragment of the invariant chain, CLIP, occupies the peptide-binding groove of the class II molecule. At endosomal pH, the binding of CLIP to human MHC class II HLA-DR molecules was counteracted by its amino-terminal segment (residues 81 to 89), which facilitated rapid release. The CLIP(81-89) fragment also catalyzed the release of CLIP(90-105) and a subset of other self-peptides, probably by transient interaction with an effector site outside the groove. Thus, CLIP may facilitate peptide loading through an allosteric release mechanism.
Gesehen am 17.07.2025